My special one. Volume 6 - Koda, Momoko; Beck, Adrienne (Shojo beat manga., 2019)
"After a mortifying rejection, Sahoko Wakaume has sworn off beautiful boys. But a chance meeting puts her in the sights of gorgeous J-pop star Kouta Kirigaya of the group Like Legend. Sahoko will need all her cynicism to defend herself against Kouta's tenderhearted and affectionate attacks to win her heart! Actress Emika Nanase is in love with idol Kanato, but she's stuck in the friend zone! When the perfect opportunity comes along -- a chance to costar with Kanato in a TV drama -- she does her best to bring the two of them closer together. But being a top-notch actress doesn't help her avoid being a total mess when she's around her crush!